51 NEUTROPHIL GELATINASE-ASSOCIATED LIPOCALIN AND INTERLEUKIN-18: EARLY, SEQUENTIAL, PREDICTIVE BIOMARKERS OF ACUTE KIDNEY INJURY AFTER CARDIAC SURGERY. (1st March 2006) - Parikh, C.; Mishra, J.; Ma, Q.; Kelly, C.; Dent, C.; Devarajan, P.; Edelstein, C.
Abstract : Purpose: Acute kidney injury (AKI) is a frequent complication of cardiopulmonary bypass (CPB). The lack of early biomarkers for AKI has impaired our ability to intervene in a timely manner. In the present study, we tested whether urinary neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18) can be combined as predictive biomarkers for diagnosis and prognosis of AKI following CPB. Methods: Serial urine samples were analyzed by ELISA for IL-18 and NGAL in 20 patients who developed AKI (defined as a 50% or greater increase in serum creatinine after CPB) and 35 controls (age-, race-, and gender-matched patients who did not develop AKI after CPB). Exclusion criteria included preexisting renal insufficiency and nephrotoxin use. Results: Using serum creatinine, AKI was detected only 48-72 hours after CPB. In contrast, NGAL increased 25-fold within 2 hours and declined after 6 hours of CPB (Lancet, 2005). Urine IL-18 increased at 4-6 hours after CPB, peaked at over 25-fold at 12 hours, and remained markedly elevated up to 48 hours after CPB. Also, on multivariate analysis, both IL-18 and NGAL were independently associated with number of days in AKI. Conclusions: Our results indicate that urinary NGAL and IL-18 are increased in tandem after CPB. The combination of these biomarkers may allow for the reliable early diagnosis and prognosis of AKI at all times after CPB, much prior to the rise in serum creatinine.